Case Report: Pericardial tamponade during left ventricular radiofrequency ablation with spontaneous hemostasis - He, Changjian; Lin, Jinming; Ding, Chunhua; Zhang, Wenchang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPericardial tamponade is a rare but life-threatening complication of catheter ablation for ventricular arrhythmias. While overt perforation—often steam-pop related—is classically implicated, alternative bleeding mechanisms are less well defined.CaseA 66-year-old man underwent left ventricular (LV) ablation for frequent idiopathic premature ventricular beats (34.3%). RF energy (30–40 W, ≤90 s) at the LV anterior wall markedly suppressed ectopy, followed by abrupt chest discomfort and hypotension. Fluoroscopy suggested pericardial effusion; emergent pericardiocentesis yielded 150 ml of bright red, arterialized blood with rapid hemodynamic recovery. Biventricular angiography showed no contrast extravasation, and serial echocardiography confirmed no recurrent effusion. The patient stabilized with indwelling drainage and was discharged uneventfully.ConclusionTamponade during LV ablation may occur without overt perforation. Prompt recognition and targeted drainage can be definitive when bleeding is self-limited.